1992
DOI: 10.1159/000133346
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of bisexual/unisexual species of <i>Poecilia</i>

Abstract: Chromosomes of Poecilia mexicana mexicana, one of the bisexual species involved in the hybrid origin of the unisexual teleost fish species P. formosa, were analyzed by several staining techniques. Sex-specific, differential heterochromatin, found in other congeneric species, was not observed in P. m. mexicana. Nucleolar organizer regions were polymorphic among individual specimens within a given population sample. A single specimen exhibiting intraindividual variability of chromosome pair 1 and a specimen with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…On the other hand, in M. edulis an alike variation was found using another banding method (DIXON et al 1986;DIXON and McFADZEN 1987). A similar behaviour could be deduced from the C-banding and Agstaining patterns of a cyprinodont fish, Poecilia latipinna (SoLA et al 1990), because when variable numbers of C-positive regions (6 to 13) were found in a population those regions were coincident with the NORs.…”
Section: Nor-associated Heterochromatic Regionssupporting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, in M. edulis an alike variation was found using another banding method (DIXON et al 1986;DIXON and McFADZEN 1987). A similar behaviour could be deduced from the C-banding and Agstaining patterns of a cyprinodont fish, Poecilia latipinna (SoLA et al 1990), because when variable numbers of C-positive regions (6 to 13) were found in a population those regions were coincident with the NORs.…”
Section: Nor-associated Heterochromatic Regionssupporting
confidence: 60%
“…On the other hand, the existence of some regions which do not C-band but are visibly heteropycnotic in the manner expected of heterochromatin, indicates that all C-bands correspond to heterochromatin but some heterochromatin is not stained by C-banding methods (SuMNER 1990). Anyway, the C-banding techni-que demonstrated that heterochromatin is subject to both qualitative and quantitative variation as well as to changes in location both within and between species (JoHN 1981;SENTis et al 1986;JoHN 1988;SoLA et al 1990;SuMNER 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal gene location polymorphism has also been seen in the gray tree frog (Hyla chrysoscelis-H. versicolor complex (Wiley et al, 1989]), as well as in a number of diverse organisms, e.g., onions (Shubert and Wobus, 1985), fish (Sola et al, 1990), and salamanders (Nardi et al, 1977). Although it is tempting to believe, based on the phylogenetic diversity of these reports, that this polymorphism is a common occurrence in eukaryotes, the general paucity of findings tends to discount that view.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, chromosomes were destained by incubation in fixative for 3 min at RT and briefly washed by distilled water. After air-drying, CMA 3 and DAPI fluorescent staining was performed sensu Sola et al [49]. Finally, the AgNO 3 staining sensu Howell and Black [50] and C-banding sensu Haaf and Schmid [51] were performed.…”
Section: Methodsmentioning
confidence: 99%